2014
DOI: 10.1177/1932296813514502
|View full text |Cite
|
Sign up to set email alerts
|

The UVA/PADOVA Type 1 Diabetes Simulator

Abstract: Recent studies have provided new insights into nonlinearities of insulin action in the hypoglycemic range and into glucagon kinetics as it relates to response to hypoglycemia. Based on these data, we developed a new version of the UVA/PADOVA Type 1 Diabetes Simulator, which was submitted to FDA in 2013 (S2013). The model of glucose kinetics in hypoglycemia has been improved, implementing the notion that insulin-dependent utilization increases nonlinearly when glucose decreases below a certain threshold. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
285
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 629 publications
(294 citation statements)
references
References 22 publications
1
285
0
8
Order By: Relevance
“…The ability of insulin to suppress the glycogenolytic response to glucagon at high insulin concentration is not reflected in previously published models of glucose-glucagon dynamics [18][19][20]. A comparative study found that a multiplicative relationship was needed to describe insulin's inhibitory effect and glucagon's stimulating effect on glycogenolysis with insulin overriding the effect of glucagon at high concentrations of both hormones [21].…”
Section: Introductionmentioning
confidence: 88%
“…The ability of insulin to suppress the glycogenolytic response to glucagon at high insulin concentration is not reflected in previously published models of glucose-glucagon dynamics [18][19][20]. A comparative study found that a multiplicative relationship was needed to describe insulin's inhibitory effect and glucagon's stimulating effect on glycogenolysis with insulin overriding the effect of glucagon at high concentrations of both hormones [21].…”
Section: Introductionmentioning
confidence: 88%
“…[3][4][5][6]), or Type 1 Diabetes cohorts (e.g. [7]). These models tend to be less complex, as metabolic measurements are minimised in clinical or outpatient settings due to clinical and patient factors such as cost, availability, or comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Первый доклинический этап тестирования эффективности и безопасности работы управляющего алгоритма принято проводить в условиях программной симуляции. Исследователи из университетов Вирджинии (США) и Падуи (Италия) разработали метаболический симулятор UVA/Padova для облегчения разработки алго-ритмов ИПЖ и их виртуального тестирования (в условиях in silico), которое по одобрению Food and Drug Administration (FDA, США) может заменить этап доклинического те-стирования с участием лабораторных животных [18][19][20].…”
Section: δP(n)=p(n)-p(n-1); δI(n)=i(n)-i(n-1); δD(n)=d(n)-d(n-1)unclassified